مدى مساهمة المؤسسات الصغيرة ومتوسطة في تحقيق التنمية المحلية - دراسة حالة الجزائر- - بطاهر, بختة; عرقوب, وعلي (جامعة الوادي - University of Eloued, 2018)
في سياق التحديات الجديدة أصبحت المؤسسات وخاصة المؤسسات الصغيرة والمتوسطة الرافد الحقيقي للتنمية محلية وذلك من خلال ما تتميز به من مرونة وقدرة على الانتشار في مختلف أقاليم البلد واستغلال موارده المحلية ، بالإضافة إلى أنها أداة فعالة في معالجة الكثير من المشكلات الاقتصادية و الاجتماعية المحلية، كالبطالة والفقر وبالتالي خلق نشاط اقتصادي محلي يساهم في استقرار السكان وتلبية حجاتهم الأساسية. In the context of new challenges institutions, especially small and medium enterprises have become the real tributary local development through what is characterized by its flexibility and ability to spread in different regions of the country and the exploitation of local resources, as well as an effective tool in dealing with a lot of economic problems and social communities, such as unemployment and poverty thus creating local economic activity contributes to their arguments and to meet the basic stability of the population.
The extent to which small and medium enterprises contribute to local development - The case study of Algeria -
مقال
Keywords: المؤسسات الصغيرة والمتوسطة، حجم العمالة، الموارد المحلية، التشغيل، الجماعات المحلية، التنمية المحلية; small and medium-sized enterprises, employment, local resource size, operating, local groups, local development.